Propagation and Purification of Baculovirus oryctes Huger - Susamto Somowiyarjo; YB Sumardiyono; Sedyo Hartono; Triharso Triharso; Jun Kobayashi (Universitas Gadjah Mada, 1995)
An isolate of Baculovirus oryctes, a possible biological control agent for coconut beetle (Oryctes rhinoceros Huger) from East Java was propagated and purified. The virus could be transmitted by feeding the imago with 10% sucrose containing virus from homogenate of infected beetles. Effectivity of virus to 9 healthy females by sexual copulation. Virus be succesfully purified by a method of Payne.